Drivers of roe deer use in fragmented forest landscapes; implications for current and future management in the context of policy driven forest expansion - Saudamini Venkatesan; Benjamin M. Marshall; Mark S. Greener; Anna Kinghorn; Isla Sligo-Young; Richard Hassall; Robin Gill; Ben McKeown; Jeanette Hall; Roman Biek; Lucy Gilbert; Thomas A. Morrison; et al. (Forest Ecology and Management, 2026)

Vancomycin-resistant Enterococcus faecium: a national wide genomic snapshot in Switzerland - Dominique S. Blanc; Florian Mauffrey; Andrea C. Büchler; Danielle Vuichard-Gysin; Vanja Piezzi; Céline Gardiol; Marc Garcia; Trestan Pillonel; Laurent Poirel; Patrice Nordmann; Pascal Schlaepfer; Claudio Neidhöfer; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

From magma to macrophage: the grand challenges of volcanic environments - Catherine A. Mériaux; Edward Ntim Gasu; Guillaume Nyagatare; Vicky Ruganzu; Philbert Ntivuguruzwa; Mwumvaneza Mutagoma; Atalay Ayele; Julyan H. E. Cartwright; Valérie Cayol; Laurent Charlet; Claudia Corradino; Antonio Costa; et al. (Bulletin of Volcanology, 2026)
The interdisciplinary study of volcanic processes, which extend across all timescales and lengths, requires a multitude of approaches, ranging from analogue and numerical modelling to observations and fieldwork and extending to mathematics. A conference was held at the East African Institute for Fundamental Research, affiliated with the University of Rwanda, a country which, along with the Democratic Republic of Congo, presents a unique geodynamic context. Located along the East African Rift, an active seismic region, Rwanda is close to two of Africa's most active volcanoes, including Nyiragongo, which overlooks Lake Kivu, a deep volcanic lake rich in dissolved carbon dioxide and methane, the latter of which is used for electricity generation. In this context, the conference addressed many “classic” volcanological topics and their modern advances, such as multiphase lava flows, subsurface magma propagation, seismic and deformation signals from a volcano, modelling of volcanic emission dispersion, and volcanic lakes. Yet, it broadened the discussion to the volcanic particle-water interface and its impact on soils, volcanoes and climate change, and volcanoes and health. This article aims to highlight and share the richness of the integration and interconnectedness of the various questions related to a volcanic environment, as well as their impact on society. Ultimately, this conference also demonstrated the importance of promoting science in Africa and developing countries so that the next generation of African researchers is equipped to address the challenges facing their nations.

Stochastic modelling of burden of livestock diseases on domestic ruminants in Ethiopia - Wudu T. Jemberu; Gemma Chaters; Theodore J.D. Knight-Jones; William Gilbert; Stephen Kwok; Mieghan Bruce; Benjamin Huntington; Jonathan Rushton (Preventive Veterinary Medicine, 2026)

Staphylococcus lugdunensis infective endocarditis: a multicentre international observational study - Benjamin Lefevre; Gilbert Habib; Bruno Hoen; Christine Selton-Suty; Mary Philip; Nahema Issa; Pierre Danneels; Marine De La Chapelle; Colin Deschanvres; Marie-Line Erpelding; Pierre Tattevin; Audrey Le Bot; et al. (Infectious Diseases, 2026)

Volcanoes to vugs: Demonstrating a FAIR geochemistry framework with a diverse application of major and trace element data through the AuScope EarthBank platform - Angus L. Nixon; Samuel C. Boone; Yoann Gréau; Fabian Kohlmann; Moritz Theile; Wayne Noble; Alexander Prent; John Foden; Steven Barnes; Ashlea N. Wainwright; Benjamin Wade; Karsten Goemann; et al. (Chemical Geology, 2025)

Trace element distributions among Cu-(Fe)-sulfides from the Olympic Dam Cu-U-Au-Ag deposit, South Australia - Samuel A. King; Nigel J. Cook; Cristiana L. Ciobanu; Kathy Ehrig; Sarah Gilbert; Benjamin Wade; Yuri T. Campo Rodriguez (Mineralium Deposita, 2025)

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

Coupled Lu-Hf and U-Pb apatite geochronology of Jatobá orebody supports ∼ 2.5 Ga metamorphism in deep shear zones from southern Copper Belt, Carajás Domain, Brazil - Yuri Tatiana Campo-Rodriguez; Cristiana L. Ciobanu; Sarah Gilbert; Benjamin Wade; Nigel J. Cook; Maria Emilia Schutesky; Kathy Ehrig (Precambrian Research, 2025)

Monazite, lanthanide-rich glasses, and other trace elements in copper smelter slags: constraints on critical metal behaviour in Si-Fe-rich melts - Hassan Gezzaz; Cristiana L. Ciobanu; Nigel J. Cook; Kathy Ehrig; Ashley Slattery; Benjamin Wade; Sarah Gilbert; Yuri T. Campo Rodriguez (Mineralogy and Petrology, 2025)
Furnace slags are potential new sources of critical metals. We undertook a micron- to nanoscale study that addresses speciation, distribution and associations of phases in air-cooled flash furnace (FF, oxidised) and electric furnace (EF, reduced) slags from the Olympic Dam mining-smelting-refinery operation. Results enable understanding of the behaviour and partitioning of critical metals between melt and cooling crystalline phases in a controlled smelter environment that mimics Fe-Si-rich systems in Nature. Melts at ~ 1300 °C result in slags that differ in the relative proportions of component phases. Both FF and EF slags comprise major magnetite and two, compositionally distinct Si-Fe-rich glasses (glass-1 and -2); fayalite is a main component of EF slag. Glass-1 is rich in REE + Y (4.5–5.4 wt%, Ce 2 O 3 + La 2 O 3 ) and contains dendritic monazite-(Ce). Glass-2 (~ 70 wt% SiO 2 ) contains < 1 wt% Ce 2 O 3 + La 2 O 3 . The EF slag reaction sequence is: magnetite $$→$$ → fayalite + glass-1 $$→$$ → monazite $$→$$ → glass-2. Immiscibility of REE-rich liquid from Si-Fe-rich melt is inferred from amorphous ‘monazite-like’ droplets. Chondrite-normalised fractionation patterns are defined by downwards-sloping LREE segments in both glasses. Partition coefficients are calculated for magnetite and fayalite relative to glasses. D REY for HREE exceeds those for LREE in all phases and fayalite has an order of magnetite higher D HREE than co-existing EF magnetite. Applying lattice strain models to experimental values show excellent fits for D HREE-model trends, even if lattice strain is not the sole factor controlling partitioning. Melt polymerisation, variable/unpredictable oxidation states, and constraints from specific crystallographic sites, also impact on observed trends. This study provides clues to element behaviour in metallurgical plants that can assist potential utilization of copper smelter slags to meet the demand for REE and other contained critical metals.

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Economic assessment of animal disease burden in Senegalese small ruminants - Anne Meyer; Bakary Ndiaye; Andrew Larkins; Gemma Chaters; William Gilbert; Benjamin Huntington; Guy Ilboudo; Michel Dione; Wudu Temesgen Jemberu; Mame Nahé Diouf; Assane Gueye Fall; Mathioro Fall; et al. (Preventive Veterinary Medicine, 2025)

Using zircon and apatite chemistry to fingerprint porphyry Cu – Mo ± Au mineralization in the Delamerian Orogen, South Australia - Wei Hong; Adrian Fabris; Sarah Gilbert; Benjamin P. Wade; Alan S. Collins; Tom Wise; Anthony J. Reid (Mineralium Deposita, 2024)
To evaluate the fertility of porphyry mineralization in the Delamerian Orogen (South Australia), zircon and apatite from four prospects, including Anabama Hill, Netley Hill, Bendigo, and Colebatch, have been analyzed by LA-ICP-MS and electron microprobe. The zircon is characterized by heavy REEs enrichment relative to light REEs, high (Ce/Nd) N (1.3–45), and weak to moderate negative Eu/Eu* (0.2–0.78). The apatite has right-sloped REE patterns with variably negative to positive Eu anomalies. Low Mg (< 670 ppm) and Sr/Y ratios (< 5) in apatite likely illustrate fractional crystallization trends for the granitic melts in shallow crust. The Yb/Gb and Eu/Eu* in zircon reveal that intrusions at Anabama Hill, Netley Hill, and Bendigo underwent fractional crystallization controlled by amphibole (< 50–60%), garnet (< 15%), apatite (< 0.6%), and/or titanite (< 0.3%). These stocks have average f O 2 values reported relative to fayalite-magnetite-quartz buffer (ΔFMQ), from 0.7 ± 0.9 to 2.1 ± 0.4, ascribed to prolonged magmatic evolution or sulfur degassing during post-subduction processes. Our data imply that both Anabama and Bendigo complexes experienced prevalent (garnet-) amphibole crystallization from hydrous melts that have moderately high oxidation (ΔFMQ + 1 to + 3) and elevated sulfur-chlorine components (Anabama, 37 ± 9 to 134 ± 83 ppm S and 0.30 ± 0.24 to 0.64 ± 0.89 wt% Cl; Bendigo, 281 ± 178 to 909 ± 474 ppm S and 0.45 ± 0.47 to 3.01 ± 1.54 wt% Cl). These are crucial ingredients to form porphyry Cu–Mo ± Au ores with economic significance, which provides encouragement for mineral exploration in this orogen.

Rationalising development of classification systems describing livestock production systems for disease burden analysis within the Global Burden of Animal Diseases programme - Yin Li; K. Marie McIntyre; Philip Rasmussen; William Gilbert; Gemma Chaters; Kassy Raymond; Wudu T. Jemberu; Andrew Larkins; Grace T. Patterson; Stephen Kwok; Alexander James Kappes; Dianne Mayberry; et al. (Research in Veterinary Science, 2024)

Approximating the global economic (market) value of farmed animals - Peggy Schrobback; Gabriel Dennis; Yin Li; Dianne Mayberry; Alexandra Shaw; Theodore Knight-Jones; Thomas Lloyd Marsh; Dustin L. Pendell; Paul R. Torgerson; William Gilbert; Benjamin Huntington; Kassy Raymond; et al. (Global Food Security, 2023)

Restoration ecology through the lens of coexistence theory - Lauren M. Hallett; Lina Aoyama; György Barabás; Benjamin Gilbert; Loralee Larios; Nancy Shackelford; Chhaya M. Werner; Oscar Godoy; Emma R. Ladouceur; Jacob E. Lucero; Christopher P. Weiss-Lehman; Jonathan M. Chase; et al. (Trends in Ecology & Evolution, 2023)

Why humans kill animals and why we cannot avoid it - Benjamin L. Allen; Christopher Bobier; Stuart Dawson; Peter J.S. Fleming; Jordan Hampton; David Jachowski; Graham I.H. Kerley; John D.C. Linnell; Kelly Marnewick; Liaan Minnie; Mike Muthersbaugh; M. Justin O'Riain; et al. (Science of The Total Environment, 2023)

Microscale THMC Modeling of Pressure Solution in Salt Rock: Impacts of Geometry and Temperature - Mengsu Hu; Carl I. Steefel; Jonny Rutqvist; Benjamin Gilbert (Rock Mechanics and Rock Engineering, 2023)
Pressure solution, a mechanism that involves tight coupling between the geometry and thermal-hydro-mechanical-chemical (THMC) processes, plays an important role in diagenesis. In this study, we make the first attempt to conduct microscale THMC modeling to understand and quantify the impacts of geometry and temperature on pressure solution, taking natural salt rock as an example. This modeling capability is achieved by expanding a novel MC code that we developed previously (Hu et al. J Geophys Res: Solid Earth 126:e2021JB023112, 2021) to include temperature effects. We first conduct a simulation of an example that involves a single brine inclusion within a single halite grain and find that the temperature impact is limited for that case. We then extract geometry from an image of a natural salt rock and conduct simulations with different cases: (A) only temperature and no stress, (B) only stress and no temperature, and (C) with both stress and temperature. These different cases result in quite different phenomena. In case A, dissolution and precipitation occur across the entire system due to isolated pore space reaching a localized mass balance between dissolution, precipitation, and diffusion. In case B, intense geometric features (e.g., major asperities, inclusions) in one area undergo stress concentration, thus dominating pressure solution in that area. In case C, pressure solution is spread out at contacting highly stressed geometric features close to the hotter side. We conclude that geometric features dominate stress distribution, thus dominating pressure solution in a natural salt rock that may be affected by the temperature if a sufficient temperature gradient is applied.

Circulating MicroRNAs Indicative of Sex and Stress in the European Seabass (Dicentrarchus labrax): Toward the Identification of New Biomarkers - Camille Houdelet; Eva Blondeau-Bidet; Mathilde Estevez-Villar; Xavier Mialhe; Sophie Hermet; François Ruelle; Gilbert Dutto; Aline Bajek; Julien Bobe; Benjamin Geffroy (Marine Biotechnology, 2023)

Phenotypic variation in the molt characteristics of a seasonal coat color-changing species reveals limited resilience to climate change - Taylor R. Peltier; Shotaro Shiratsuru; Benjamin Zuckerberg; Mark Romanski; Lynette Potvin; Andrew Edwards; Jonathan H. Gilbert; Tanya R. Aldred; Ann Dassow; Jonathan N. Pauli (Oecologia, 2023)

Daily activity timing in the Anthropocene - Neil A. Gilbert; Kate A. McGinn; Laura A. Nunes; Amy A. Shipley; Jacy Bernath-Plaisted; John D.J. Clare; Penelope W. Murphy; Spencer R. Keyser; Kimberly L. Thompson; Scott B. Maresh Nelson; Jeremy M. Cohen; Ivy V. Widick; et al. (Trends in Ecology & Evolution, 2023)

Mineralogical, magnetic and geochemical data constrain the pathways and extent of weathering of mineralized sedimentary rocks - Sergio Carrero; Sarah P. Slotznick; Sirine C. Fakra; M. Cole Sitar; Sharon E. Bone; Jeffrey L. Mauk; Andrew H. Manning; Nicholas L. Swanson-Hysell; Kenneth H Williams; Jillian F. Banfield; Benjamin Gilbert (Geochimica et Cosmochimica Acta, 2023)

Biodiversity patterns diverge along geographic temperature gradients - Charlie J. G. Loewen; Donald A. Jackson; Benjamin Gilbert (Global Change Biology, 2023)
Models applying space‐for‐time substitution, including those projecting ecological responses to climate change, generally assume an elevational and latitudinal equivalence that is rarely tested. However, a mismatch may lead to different capacities for providing climatic refuge to dispersing species. We compiled community data on zooplankton, ectothermic animals that form the consumer basis of most aquatic food webs, from over 1200 mountain lakes and ponds across western North America to assess biodiversity along geographic temperature gradients spanning nearly 3750 m elevation and 30° latitude. Species richness, phylogenetic relationships, and functional diversity all showed contrasting responses across gradients, with richness metrics plateauing at low elevations but exhibiting intermediate latitudinal maxima. The nonmonotonic/hump‐shaped diversity trends with latitude emerged from geographic interactions, including weaker latitudinal relationships at higher elevations (i.e. in alpine lakes) linked to different underlying drivers. Here, divergent patterns of phylogenetic and functional trait dispersion indicate shifting roles of environmental filters and limiting similarity in the assembly of communities with increasing elevation and latitude. We further tested whether gradients showed common responses to warmer temperatures and found that mean annual (but not seasonal) temperatures predicted elevational richness patterns but failed to capture consistent trends with latitude, meaning that predictions of how climate change will influence diversity also differ between gradients. Contrasting responses to elevation‐ and latitude‐driven warming suggest different limits on climatic refugia and likely greater barriers to northward range expansion.

Aerobic respiration controls on shale weathering - Lucien Stolze; Bhavna Arora; Dipankar Dwivedi; Carl Steefel; Zhi Li; Sergio Carrero; Benjamin Gilbert; Peter Nico; Markus Bill (Geochimica et Cosmochimica Acta, 2023)

Extinction dynamics: The interplay of species traits and the spatial scales of metapopulation declines - Emma J. Walker; Benjamin Gilbert (Ecology, 2023)
Global changes can lead to species declines and extinctions through their impacts on species habitats at two distinct spatial scales: habitat destruction, in which individual habitat patches are destroyed by land‐use change or natural disasters, and habitat degradation, in which larger scale changes, such as nitrogen deposition or climate change, lower mean population abundances across landscapes. We developed a theory showing that, even when these two forms of global change have an identical impact on a species' total amount of habitat, they have qualitatively different consequences for species dynamics and extinction. Using metapopulation theory and simulations, we found distinct impacts of these global changes characterized through several responses: the rate at which populations are lost from the remaining patches, extinction thresholds, and the duration of extinction debts. Habitat degradation causes a faster decline in species populations when habitat reduction is low, making it particularly detrimental for rare species. Habitat destruction has smaller impacts for low habitat reduction, but shows clear thresholds beyond which it surpasses degradation's negative impact; the location and steepness of the threshold depends on species dispersal, with poor dispersers having steeper thresholds. These results highlight the challenge of using population monitoring to assess the consequences of global changes and predict consequences of further change: extinction trajectories cannot be predicted due to thresholds (habitat destruction) and lagged dynamics that lead to extinction debts (habitat degradation). Our research clarifies why the impacts of one type of global change may poorly predict the impacts of the other and suggests general rules for predicting the long‐term impacts of global changes based on species traits.

Evolution of a hydrothermal ore-forming system recorded by sulfide mineral chemistry: a case study from the Plaka Pb–Zn–Ag Deposit, Lavrion, Greece - Max Frenzel; Panagiotis Voudouris; Nigel J. Cook; Cristiana L. Ciobanu; Sarah Gilbert; Benjamin P. Wade (Mineralium Deposita, 2022)
Laser ablation-inductively coupled plasma-mass spectrometry and electron-probe microanalysis were used to investigate the trace-element contents of sphalerite, chalcopyrite and pyrite from the Plaka Pb–Zn–Ag deposit. Using petrographic observations, the analytical results could be linked to the temporal evolution of the Plaka ore-forming system. Sphalerite chemistry reliably records the temperature and f S 2 evolution of the system, with estimated formation temperatures reproducing the microthermometric results from previous fluid-inclusion studies. Chalcopyrite chemistry also shows systematic variations over time, particularly for Cd, Co, Ge, In, Sn and Zn concentrations. Measurable pyrite was only found in association with early high-temperature mineralisation, and no clear trends could therefore be identified. We note, however, that As and Se contents in pyrite are consistent with formation temperatures estimated from co-existing sphalerite. Statistical analysis of the sphalerite data allowed us to identify the dominant geological controls on its trace-element content. The three investigated factors temperature, f S 2 , and sample location account for > 80% of the observed variance in Mn, Fe, Co, Ga, Ge, In, Sb and Hg concentrations, and > 60% of the observed variance in Cd and Sn concentrations. Only for Cu and Ag concentrations is the explained variance < 50%. A similarly detailed analysis was not possible for chalcopyrite and pyrite. Nevertheless, comparison of the results for all three investigated minerals indicates that there are some systematic variations across the deposit which may be explained by local differences in fluid composition.

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

Abundance estimation of unmarked animals based on camera‐trap data - Neil A. Gilbert; John D. J. Clare; Jennifer L. Stenglein; Benjamin Zuckerberg (Conservation Biology, 2021)
The rapid improvement of camera traps in recent decades has revolutionized biodiversity monitoring. Despite clear applications in conservation science, camera traps have seldom been used to model the abundance of unmarked animal populations. We sought to summarize the challenges facing abundance estimation of unmarked animals, compile an overview of existing analytical frameworks, and provide guidance for practitioners seeking a suitable method. When a camera records multiple detections of an unmarked animal, one cannot determine whether the images represent multiple mobile individuals or a single individual repeatedly entering the camera viewshed. Furthermore, animal movement obfuscates a clear definition of the sampling area and, as a result, the area to which an abundance estimate corresponds. Recognizing these challenges, we identified 6 analytical approaches and reviewed 927 camera‐trap studies published from 2014 to 2019 to assess the use and prevalence of each method. Only about 5% of the studies used any of the abundance‐estimation methods we identified. Most of these studies estimated local abundance or covariate relationships rather than predicting abundance or density over broader areas. Next, for each analytical approach, we compiled the data requirements, assumptions, advantages, and disadvantages to help practitioners navigate the landscape of abundance estimation methods. When seeking an appropriate method, practitioners should evaluate the life history of the focal taxa, carefully define the area of the sampling frame, and consider what types of data collection are possible. The challenge of estimating abundance of unmarked animal populations persists; although multiple methods exist, no one method is optimal for camera‐trap data under all circumstances. As analytical frameworks continue to evolve and abundance estimation of unmarked animals becomes increasingly common, camera traps will become even more important for informing conservation decision‐making.

A Review of Overlapping Landscapes: Pseudoreplication or a Red Herring in Landscape Ecology? - Benjamin Zuckerberg; Jeremy M. Cohen; Laura A. Nunes; Jacy Bernath-Plaisted; John D. J. Clare; Neil A. Gilbert; Sofia S. Kozidis; Scott B. Maresh Nelson; Amy A. Shipley; Kimberly L. Thompson; André Desrochers (Current Landscape Ecology Reports, 2020)

Climate warming moderates the impacts of introduced sportfish on multiple dimensions of prey biodiversity - Charlie J. G. Loewen; Angela L. Strecker; Benjamin Gilbert; Donald A. Jackson (Global Change Biology, 2020)
Human‐assisted introductions of exotic species are a leading cause of anthropogenic change in biodiversity; however, context dependencies and interactions with co‐occurring stressors impede our ability to predict their ecological impacts. The legacy of historical sportfish stocking in mountainous regions of western North America creates a unique, natural quasiexperiment to investigate factors moderating invasion impacts on native communities across broad geographic and environmental gradients. Here we synthesize fish stocking records and zooplankton relative abundance for 685 mountain lakes and ponds in the Cascade and Canadian Rocky Mountain Ranges, to reveal the effects of predatory sportfish introduction on multiple taxonomic, functional and phylogenetic dimensions of prey biodiversity. We demonstrate an innovative analytical approach, combining exploratory random forest machine learning with confirmatory multigroup analysis using multivariate partial least‐squares structural equation models, to generate and test hypotheses concerning environmental moderation of stocking impacts. We discovered distinct effects of stocking across different dimensions of diversity, including negligible (nonsignificant) impacts on local taxonomic richness (i.e. alpha diversity) and trophic structure, in contrast to significant declines in compositional uniqueness (i.e. beta diversity) and body size. Furthermore, we found that stocking impacts were moderated by cross‐scale interactions with climate and climate‐related land‐cover variables (e.g. factors linked to treeline position and glaciers). Interactions with physical morphometric and lithological factors were generally of lesser importance, though catchment slope and habitat size constraints were relevant in certain dimensions. Finally, applying space‐for‐time substitution, a strong antagonistic (i.e. dampening) interaction between sportfish predation and warmer temperatures suggests redundancy of their size‐selective effects, meaning that warming will lessen the consequences of introductions in the future and stocked lakes may be less impacted by subsequent warming. While both stressors drive biotic homogenization, our results have important implications for fisheries managers weighing the costs/benefits of stocking—or removing established non‐native populations—under a rapidly changing climate.

Climate and local environment structure asynchrony and the stability of primary production in grasslands - Benjamin Gilbert; Andrew S. MacDougall; Taku Kadoya; Munemitsu Akasaka; Joseph R. Bennett; Eric M. Lind; Habacuc Flores‐Moreno; Jennifer Firn; Yann Hautier; Elizabeth T. Borer; Eric W. Seabloom; Peter B. Adler; et al. (Global Ecology and Biogeography, 2020)
Aim Climate variability threatens to destabilize production in many ecosystems. Asynchronous species dynamics may buffer against such variability when a decrease in performance by some species is offset by an increase in performance of others. However, high climatic variability can eliminate species through stochastic extinctions or cause similar stress responses among species that reduce buffering. Local conditions, such as soil nutrients, can also alter production stability directly or by influencing asynchrony. We test these hypotheses using a globally distributed sampling experiment. Location Grasslands in North America, Europe and Australia. Time period Annual surveys over 5 year intervals occurring between 2007 and 2014. Major taxa studied Herbaceous plants. Methods We sampled annually the per species cover and aboveground community biomass [net primary productivity (NPP)], plus soil chemical properties, in 29 grasslands. We tested how soil conditions, combined with variability in precipitation and temperature, affect species richness, asynchrony and temporal stability of primary productivity. We used bivariate relationships and structural equation modelling to examine proximate and ultimate relationships. Results Climate variability strongly predicted asynchrony, whereas NPP stability was more related to soil conditions. Species richness was structured by both climate variability and soils and, in turn, increased asynchrony. Variability in temperature and precipitation caused a unimodal asynchrony response, with asynchrony being lowest at low and high climate variability. Climate impacted stability indirectly, through its effect on asynchrony, with stability increasing at higher asynchrony owing to lower inter‐annual variability in NPP. Soil conditions had no detectable effect on asynchrony but increased stability by increasing the mean NPP, especially when soil organic matter was high. Main conclusions We found globally consistent evidence that climate modulates species asynchrony but that the direct effect on stability is low relative to local soil conditions. Nonetheless, our observed unimodal responses to variability in temperature and precipitation suggest asynchrony thresholds, beyond which there are detectable destabilizing impacts of climate on primary productivity.

Species niches, not traits, determine abundance and occupancy patterns: A multi‐site synthesis - Nicholas A. C. Marino; Régis Céréghino; Benjamin Gilbert; Jana S. Petermann; Diane S. Srivastava; Paula M. de Omena; Fabiola Ospina Bautista; Laura Melissa Guzman; Gustavo Q. Romero; M. Kurtis Trzcinski; Ignacio M. Barberis; Bruno Corbara; et al. (Global Ecology and Biogeography, 2020)
Aim Locally abundant species are usually widespread, and this pattern has been related to properties of the niches and traits of species. However, such explanations fail to account for the potential of traits to determine species niches and often overlook statistical artefacts. Here, we examine how trait distinctiveness determines the abilities of species to exploit either common habitats (niche position) or a range of habitats (niche breadth) and how niche position and breadth, in turn, affect abundance and occupancy. We also examine how statistical artefacts moderate these relationships. Location Sixteen sites in the Neotropics. Time period 1993–2014. Major taxa studied Aquatic invertebrates from tank bromeliads. Methods We measured the environmental niche position and breadth of each species and calculated its trait distinctiveness as the average trait difference from all other species at each site. Then, we used a combination of structural equation models and a meta‐analytical approach to test trait–niche relationships and a null model to control for statistical artefacts. Results The trait distinctiveness of each species was unrelated to its niche properties, abundance and occupancy. In contrast, niche position was the main predictor of abundance and occupancy; species that used the most common environmental conditions found across bromeliads were locally abundant and widespread. Contributions of niche breadth to such patterns were attributable to statistical artefacts, indicating that effects of niche breadth might have been overestimated in previous studies. Main conclusions Our study reveals the generality of niche position in explaining one of the most common ecological patterns. The robustness of this result is underscored by the geographical extent of our study and our control of statistical artefacts. We call for a similar examination across other systems, which is an essential task to understand the drivers of commonness across the tree of life.

Expression of Concern: Trait variation across biological scales shapes community structure and ecosystem function - Denon Start; Benjamin Gilbert (Ecology, 2019)
Trait variation underlies our understanding of the patterns and importance of biodiversity, yet we have a poor understanding of how variation at different levels of biological organization structures communities and ecosystems. Here, we use a mesocosm experiment to test for the effects of a larval dragonfly functional trait on community and ecosystem dynamics by creating artificial populations to mirror within‐ and between‐population trait variation observed in our study area. Specifically, we manipulate variation in activity rate, a key functional trait shaping food webs, across three levels of biological organization: within‐populations (differences in trait variation in a population), among‐populations (differences in population mean trait values), and among‐species (species‐level differences of co‐occurring dragonflies). We show that differences in activity rate alter prey communities, trophic cascades, and multiple ecosystem processes. However, trait variation among populations had much larger effects than differences between co‐occurring species or even the presence of a predator, whereas within‐population variation had a relatively minor impact. Interestingly, combined with earlier work in the same system, our study suggests that the relative importance of species vs. individual level differences for ecosystem functioning will depend on the spatial scale considered. Ecological processes, including biodiversity–ecosystem‐functioning relationships, cannot be understood without accounting for trait variation across biological scales of organization, including at fine scales.

Obituary: Siv Aina Jensen Leendertz (Born Siv Aina Jensen: 1973–2018) - Chantal Akoua-Koffi; Sandra Beermann; Sébastien Calvignac-Spencer; Emmanuel Couacy-Hymann; Helene De Nys; Bernhard Ehlers; Thomas Gillespie; Jeffrey Gilbert; Jan F. Gogarten; Sandra J. Laney; Felix Lankester; Fabian H. Leendertz; et al. (International Journal of Primatology, 2018)

Multi‐scale responses to warming in an experimental insect metacommunity - Tess Nahanni Grainger; Benjamin Gilbert (Global Change Biology, 2017)
In metacommunities, diversity is the product of species interactions at the local scale and dispersal between habitat patches at the regional scale. Although warming can alter both species interactions and dispersal, the combined effects of warming on these two processes remains uncertain. To determine the independent and interactive effects of warming‐induced changes to local species interactions and dispersal, we constructed experimental metacommunities consisting of enclosed milkweed patches seeded with five herbivorous milkweed specialist insect species. We treated metacommunities with two levels of warming (unwarmed and warmed) and three levels of connectivity (isolated, low connectivity, high connectivity). Based on metabolic theory, we predicted that if plant resources were limited, warming would accelerate resource drawdown, causing local insect declines and increasing both insect dispersal and the importance of connectivity to neighboring patches for insect persistence. Conversely, given abundant resources, warming could have positive local effects on insects, and the risk of traversing a corridor to reach a neighboring patch could outweigh the benefits of additional resources. We found support for the latter scenario. Neither resource drawdown nor the weak insect‐insect associations in our system were affected by warming, and most insect species did better locally in warmed conditions and had dispersal responses that were unchanged or indirectly affected by warming. Dispersal across the matrix posed a species‐specific risk that led to declines in two species in connected metacommunities. Combined, this scaled up to cause an interactive effect of warming and connectivity on diversity, with unwarmed metacommunities with low connectivity incurring the most rapid declines in diversity. Overall, this study demonstrates the importance of integrating the complex outcomes of species interactions and spatial structure in understanding community response to climate change.

Natural products and phytotherapy: an innovative perspective in leishmaniasis treatment - Luiz Filipe Gonçalves de Oliveira; Bernardo Acácio Santini Pereira; Benjamin Gilbert; Arthur Luiz Corrêa; Leandro Rocha; Carlos Roberto Alves (Phytochemistry Reviews, 2017)

Predator personality structures prey communities and trophic cascades - Denon Start; Benjamin Gilbert (Ecology Letters, 2017)
Intraspecific variation is central to our understanding of evolution and population ecology, yet its consequences for community ecology are poorly understood. Animal personality – consistent individual differences in suites of behaviours – may be particularly important for trophic dynamics, where predator personality can determine activity rates and patterns of attack. We used mesocosms with aquatic food webs in which the top predator (dragonfly nymphs) varied in activity and subsequent attack rates on zooplankton, and tested the effects of predator personality. We found support for four hypotheses: (1) active predators disproportionately reduce the abundance of prey, (2) active predators select for predator‐resistant prey species, (3) active predators strengthen trophic cascades (increase phytoplankton abundance) and (4) active predators are more likely to cannibalise one another, weakening all other trends when at high densities. These results suggest that intraspecific variation in predator personality is an important determinant of prey abundance, community composition and trophic cascades.

Predators modify biogeographic constraints on species distributions in an insect metacommunity - Tess Nahanni Grainger; Rachel M. Germain; Natalie T. Jones; Benjamin Gilbert (Ecology, 2017)
Theory describing the positive effects of patch size and connectivity on diversity in fragmented systems has stimulated a large body of empirical work, yet predicting when and how local species interactions mediate these responses remains challenging. We used insects that specialize on milkweed plants as a model metacommunity to investigate how local predation alters the effects of biogeographic constraints on species distributions. Species‐specific dispersal ability and susceptibility to predation were used to predict when patch size and connectivity should shape species distributions, and when these should be modified by local predator densities. We surveyed specialist herbivores and their predators in milkweed patches in two matrix types, a forest and an old field. Predator‐resistant species showed the predicted direct positive effects of patch size and connectivity on occupancy rates. For predator‐susceptible species, predators consistently altered the impact of biogeographic constraints, rather than acting independently. Finally, differences between matrix types in species’ responses and overall occupancy rates indicate a potential role of the inter‐patch environment in mediating the joint effects of predators and spatial drivers. Together, these results highlight the importance of local top‐down pressure in mediating classic biogeographic relationships, and demonstrate how species‐specific responses to local and regional constraints can be used to predict these effects.

Biotic forcing: the push–pull of plant ranges - Natalie T. Jones; Benjamin Gilbert (Plant Ecology, 2016)

Contrasting beta diversity among regions: how do classical and multivariate approaches compare? - Joseph R. Bennett; Benjamin Gilbert (Global Ecology and Biogeography, 2016)
Aim Approaches to calculating beta diversity (β) include classical measures based on alpha (α) and gamma (γ) diversity, and multivariate distance‐based measures. Species–area relationships cause measurements of γ to vary, making comparisons of classical β among regions contingent on sampling effort. A recent null‐modelling approach has attempted to account for variation in γ by calculating the degree to which β deviates from a random expectation. Here, we clarify the mathematical links between classical and multivariate approaches to measuring β, to derive predictions regarding the reliability of classical, null‐model and multivariate approaches. Next, we use four ecological datasets and simulated data to test the consistency of these approaches across sampling effort and γ. We focus on an issue that arises when making comparisons among regions, namely that even small changes to the area sampled can differentially increase measured γ in each region, potentially causing artefacts in β that are driven by methodology rather than biology. Innovation Comparisons among regions using classical and null‐model measures change dramatically as sampling effort and γ increase. This change is understood for classical β because of species–area relationships, but not for null‐model measures, making comparisons among regions impossible using the null‐model approach. Multiple‐site dissimilarity shows a similar sensitivity to γ as classical measures. In contrast, pairwise multivariate distances show no systematic effect of sampling effort and γ: increasing the number of sample plots decreases variability but does not alter mean β. Main conclusions Multivariate pairwise distances are independent of sample size, offering the most robust comparison among regions. The widespread influence of sampling effort and γ indicate that only scale‐dependent measures of classical and multiple‐site β are comparable, whereas null‐model β may not be comparable among regions. However, in cases where γ is well known, multiple‐site dissimilarity metrics offer several advantages, and should be strongly considered.

Molecular structure of glycogen in diabetic liver - Bin Deng; Mitchell A. Sullivan; Jialun Li; Xinle Tan; Chengjun Zhu; Benjamin L. Schulz; Robert G. Gilbert (Glycoconjugate Journal, 2015)

Historical anthropogenic disturbances influence patterns of non-native earthworm and plant invasions in a temperate primary forest - Robin Beauséjour; I. Tanya Handa; Martin J. Lechowicz; Benjamin Gilbert; Mark Vellend (Biological Invasions, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

A bioenergetic framework for the temperature dependence of trophic interactions - Benjamin Gilbert; Tyler D. Tunney; Kevin S. McCann; John P. DeLong; David A. Vasseur; Van Savage; Jonathan B. Shurin; Anthony I. Dell; Brandon T. Barton; Christopher D.G. Harley; Heather M. Kharouba; Pavel Kratina; et al. (Ecology Letters, 2014)
Changing temperature can substantially shift ecological communities by altering the strength and stability of trophic interactions. Because many ecological rates are constrained by temperature, new approaches are required to understand how simultaneous changes in multiple rates alter the relative performance of species and their trophic interactions. We develop an energetic approach to identify the relationship between biomass fluxes and standing biomass across trophic levels. Our approach links ecological rates and trophic dynamics to measure temperature‐dependent changes to the strength of trophic interactions and determine how these changes alter food web stability. It accomplishes this by using biomass as a common energetic currency and isolating three temperature‐dependent processes that are common to all consumer–resource interactions: biomass accumulation of the resource, resource consumption and consumer mortality. Using this framework, we clarify when and how temperature alters consumer to resource biomass ratios, equilibrium resilience, consumer variability, extinction risk and transient vs. equilibrium dynamics. Finally, we characterise key asymmetries in species responses to temperature that produce these distinct dynamic behaviours and identify when they are likely to emerge. Overall, our framework provides a mechanistic and more unified understanding of the temperature dependence of trophic dynamics in terms of ecological rates, biomass ratios and stability.

Hidden responses to environmental variation: maternal effects reveal species niche dimensions - Rachel M. Germain; Benjamin Gilbert (Ecology Letters, 2014)
Species responses to fluctuating environments structure population and community dynamics in variable ecosystems. Although offspring number is commonly used to measure these responses, maternal effects on offspring quality may be an important but largely unrecognised determinant of long‐term population growth. We selected 29 species across a Mediterranean annual plant phylogeny, and grew populations of each species in wet and dry conditions to determine responses in seed number and maternal effects (seed size, seed dormancy, and seedling growth). Maternal effects were evident in over 40% of species, but only 24% responded through seed number. Despite a strong trade‐off between seed size and seed number among species, there was no consistent trade‐off within species; we observed correlations that ranged from positive to negative. Overall, species in this plant guild show a complex range of responses to environmental variation that may be underestimated when only seed number responses are considered.

Combining Ecological Classification Systems and Conservation Filters Could Facilitate the Integration of Wildlife and Forest Management - Eric K. Zenner; JeriLynn E. Peck; Kristen Brubaker; Benjamin Gamble; Carrie Gilbert; Daniel Heggenstaller; Jeanne Hickey; Kelly Sitch; Robbie Withington (Journal of Forestry, 2010)
Ecosystem management demands simultaneous consideration and integration of ecosystem services in monitoring, planning, and management activities, but specialization has led to independently developed traditions in wildlife biology and management and forestry. We drew on the literature to explore the use of filters in wildlife conservation and ecological classification systems in forest management and to ask the question, “Can combining these tools improve our integration of wildlife and forest management?” Although each tool has been successfully applied independently, relatively few examples still exist for their combined use. We conclude that this approach has potential for enhancing research, monitoring, and management in areas beyond wildlife management, including forest health.

Domain-wide regulation of DNA replication timing during mammalian development - Benjamin D. Pope; Ichiro Hiratani; David M. Gilbert (Chromosome Research, 2010)

Thuja plicata exclusion in ectomycorrhiza-dominated forests: testing the role of inoculum potential of arbuscular mycorrhizal fungi - Adrian Weber; Justine Karst; Benjamin Gilbert; J. P. Kimmins (Oecologia, 2005)

Evidence of homing behavior in the coral reef mysid Mysidium gracile - Benjamin S. Twining; John J. Gilbert; Nicholas S. Fisher (Limnology and Oceanography, 2000)
Mysid swarms at benthic coral reef sites disperse into the water column in the evening and reform at the exact same location the following morning, possibly reflecting homing behavior of individual mysids. To facilitate tracking of individual mysids, we radiolabeled part of a swarm of Mysidium gracile with the gamma‐emitting radioisotope 65 Zn and released the labeled animals back to the focal swarm on a reef in Discovery Bay, Jamaica. We collected the focal swarm and surrounding swarms the next morning to determine the location of the labeled individuals following nighttime dispersal. Seventy‐seven percent of the radiolabeled mysids returned to the same site the next day, and 13% of the labeled individuals were recovered from other nearby swarms. This recovery rate cannot be attributed to random reaggregation and suggests that mysids use a homing behavior to facilitate swarm reformation. This is the first unequivocal evidence of homing behavior in demersal zooplankton.